PENGARUH PEMBELAJARAN DI DALAM KELAS TERHADAP PEMBENTUKAN KARAKTER SISWA SDN DI SDN 032 KUALU TAMBANG KABUPATEN KAMPAR - Siti Habibah; Ahmad Eddison; Hambali Hambali (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: This study aims to analyze and determine the effect of learning in the classroom on the character formation of students in SDN 032 Kualu Tambang Kampar Regency. The subjects of this study were teachers at SDN 032 Kualu Tambang Kabupaten Kampar. This study, sample of 29 respondent were selected. This study uses a simple linear analysis, using primary data by testing using SPSS 17. Based on the analysis conducted, the results obtained by testing the hypothesis of learning variables in the classroom (X) on the positive and significant character of students (Y), it can be drawn that good learning in the classroom given by the teacher in the classroom, the better the character of students is awakened.The teacher has a big role in providing learning about the development of the characteristics that are able to be accepted by students, because with good learning in the classroom accompanied by real examples that can be used as a reference to students as learning material to build character, this character is built not only for students to other students, but the student's character to the teacher, the school environment, parents or family, and the home environmentKey Words: Learning in the Classroom, Student Character